Sternopleural is a regulatory mutation of wingless with both dominant and recessive effects on larval development of Drosophila melanogaster. - Neumann, C.J.; Cohen, S.M. (Genetics, 1996)
The Drosophila wingless (wg) gene encodes a secreted signaling protein that is required for many separate patterning events in both embryonic and larval development. wg functions in the development of the adult structures have been studied using the conditional mutant wgts and also using regulatory mutations of wg that reduce larval functions. Here we present evidence that Sternopleural (Sp) is another regulatory allele of wg that affects a subset of larval functions. Sp has both a recessive loss-of-function component and a gain-of-function component. The loss-of-function component reflects a reduction of wg activity in the notum and in the antenna. The gain-of-function component apparently leads to ectopic wg activity in the dorsal first and second leg disc and thereby generates the dominant Sp phenotype. Sp and other wg alleles show a complex pattern of complementation. We present evidence that these genetic properties are due to transvection. These results have implications for the genetic definition of a null allele at loci subject to transvection.